Adropin Is a Key Mediator of Hypoxia Induced Anti-Dipsogenic Effects via TRPV4-CamKK-AMPK Signaling in the Circumventricular Organs of Rats - Yang, Fan; Zhou, Li; Qian, Xu; Wang, Dong; He, Wen-Juan; Tang, Zhong-wei; Yin, Jun; Huang, Qing-Yuan (Frontiers in Molecular Neuroscience, 2017)
Water intake reduction (anti-dipsogenic effects) under hypoxia has been well established, but the underlying reason remains unknown. Our previous report indicated that activated TRPV4 neurons in SFO are associated with anti-dipsogenic effects under hypoxia. Although low partial pressure of blood oxygen directly activates TRPV4, humoral factors could also be involved. In the present study, we hypothesis that adropin, a new endogenous peptide hormone, was rapidly increased (serum and brain) concomitant with reduced water intake in early hypoxia. Also, the nuclear expression of c-Fos, a marker for neuronal activation, related to water-consumption (SFO and MnPO) was inhibited. These effects were mitigated by a scavenger, rat adropin neutralizing antibody, which effectively neutralized adropin under hypoxia. Interestingly, injection of recombinant adropin in the third ventricle of the rats also triggered anti-dipsogenic effects and reduced c-Fos positive cells in SFO, but these effects were absent when TRPV4 was knocked down by shRNA. Moreover, adropin-activated CamKK-AMPK signaling related to TRPV4 calcium channel in SFO in normoxia. These results revealed that dissociative adropin was elevated in acute hypoxia, which was responsible for anti-dipsogenic effects by altering TRPV4-CamKK-AMPK signaling in SFO.